Gut fungi differentially response to the antipyretic (heat-clearing) and diaphoretic (exterior-releasing) traditional Chinese medicines in Coptis chinensis-conditioned gut microbiota - Yang, Yanan; Lu, Weiying; Zhang, Xiaopo; Wu, Chongming (Frontiers in Pharmacology, 2022)
Antipyretic (heat-clearing) and diaphoretic (exterior-releasing) drugs are two main groups of traditional Chinese medicines (TCMs) possessing anti-microbes and anti-inflammation effects, with the former mainly through clearing pyrogens while the latter through promoting diaphoresis. Although anti-microorganism is a common action of these two kinds of TCMs, their difference in antimicrobial spectrums and their interactions when combinedly used remain unclear. Herein, we prepared aqueous extracts from Coptis chinensis (HL) and other antipyretic or diaphoretic TCMs, orally administrated them to C57BL/6 mice at a clinical dose for fourteen days, and analyzed their impaction on both gut bacteria and fungi using full-length 16 S rRNA gene sequencing and internal transcribed spacer 1/2 (ITS1/2) gene sequencing, respectively. Oral administration of HL significantly changed the structure of gut bacteria but showed little influence on gut fungi. Co-treatment with antipyretic or diaphoretic TCMs alleviated the impact of HL on gut bacteria to a similar degree. However, combined with either heat-clearing or exterior-releasing TCMs significantly strengthened the influence of HL on gut fungi, with the latter superior to the former. The antipyretic TCMs enriched Penicillium spp. while diaphoretic TCMs promoted Fusarium spp. Further analysis revealed that the diaphoretic TCMs-enriched fungi Fusarium spp. were positively related to Akkermansia spp., a beneficial bacterium that interacts with Toll-like receptor 4 (TLR4) and regulates thermogenesis, thus providing a potential linkage with their pro-diaphoresis effect. Together, our results reveal that gut fungi differentially respond to the impact of heat-clearing and exterior-releasing TCMs on Coptis chinensis-conditioned gut microbiota, which provides insights into their functional characteristics.